Comparison of Work Motivation and Working Conditions to The Performance of Msmes Employees Before and During Covid-19 - Dwi Cahya, Agus; Disfantoro, Bagus; Khusniah, Khusniah (universitas Pamulang, 2021)
â€œThe purpose of this study was to compare the effect of work motivation and working conditions on the performance of MSME employees before and during the Covid-19 pandemic. The researcher uses a comparative research type with a quantitative approach. Techniques Data collection is done using a questionnaire with the linkert method. And the sampling technique used is to use a saturated sample (total sampling). The total sample obtained is 37 employees from several MSMEs. In the test of the effect of work motivation, work motivation has no significant effect on employee performance. Variable working conditions have a significant effect on employee performance. In the F test there is an influence between work motivation and working conditions on employee performance. And in the comparison test, there is a significant difference between work motivation and working conditions before and during covid-19. While in the employee performance variable there is no significant difference between employee performance before and during Covid-19â€.